The Impact of Financial Technology Payment on Bank Fee-Based Income - Surahmi Kando; Irwan Trinugroho (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2022)
This study investigates the effect of the growth of financial technology payment on bank fee-based income by studying conventional banks in Indonesia from 2012 to 2019. We employ Random Effect (RE) to estimate our empirical model. Fintech payment is measured by using the log of volume transactions made by fintech payment firms. Our result shows a negative and significant relationship between fintech payment and bank fee-based income. This result indicating that, in general, fintech payment disrupts banks’ fee based-income. In particular, we find that fintech is a complement for small commercial banks.How to Cite:Kando, S., & Trinugroho, I. (2022). The Impact of Fintech Payment on Bank Fee-Based Income. Signifikan: Jurnal Ilmu Ekonomi, 11(2), 425-436. https://doi.org/10.15408/sjie.v11i2.26809.JEL Classification: G18, G21, G28